High-Throughput sequencing reveals circulating miRNAs as potential biomarkers of kidney damage in patients with systemic lupus erythematosus (2016)
Estudio exploratorio que busca identificar mirnas expresados diferenciamente en con lupus eritematoso sistemico que presentan alteraciones renales.